2022
DOI: 10.3390/cancers14020436
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Prospective Whole Genome Sequencing in Sarcoma Patients

Abstract: With more than 70 different histological sarcoma subtypes, accurate classification can be challenging. Although characteristic genetic events can largely facilitate pathological assessment, large-scale molecular profiling generally is not part of regular diagnostic workflows for sarcoma patients. We hypothesized that whole genome sequencing (WGS) optimizes clinical care of sarcoma patients by detection of diagnostic and actionable genomic characteristics, and of underlying hereditary conditions. WGS of tumor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(47 reference statements)
0
8
0
Order By: Relevance
“… 26 A recent clinical WGS study of 83 patients with sarcoma demonstrated refinement of diagnosis in 14% of cases, nomination of actionable biomarkers in 36% of tumors, and detection of germline cancer predisposition variants in 8% of patients. 27 WGS may be particularly impactful in sarcoma given its position as one of the most heterogeneous of all cancers, with the newest WHO classification denoting 175 different soft tissue and bone tumors, many distinguishable by genomic features. 28 , 29 WGTS may also prevent patients from being misassigned to therapies that are unlikely to provide any efficacy while at the same time bringing considerable clinical toxicity to patients and financial burden to the health care system.…”
Section: Resultsmentioning
confidence: 99%
“… 26 A recent clinical WGS study of 83 patients with sarcoma demonstrated refinement of diagnosis in 14% of cases, nomination of actionable biomarkers in 36% of tumors, and detection of germline cancer predisposition variants in 8% of patients. 27 WGS may be particularly impactful in sarcoma given its position as one of the most heterogeneous of all cancers, with the newest WHO classification denoting 175 different soft tissue and bone tumors, many distinguishable by genomic features. 28 , 29 WGTS may also prevent patients from being misassigned to therapies that are unlikely to provide any efficacy while at the same time bringing considerable clinical toxicity to patients and financial burden to the health care system.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, many sarcoma subtypes have been grouped together for diagnosis and treatment purposes, leading to suboptimal outcomes. Recent studies have highlighted the importance of molecular characterization to improve diagnostic accuracy and impact treatment plans [8] . At present, the use of NGS in soft tissue sarcomas has not been defined but is likely to become more widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Three patients have been described elsewhere. 16 CUPs were defined as tumors with unknown origin or histological type. CUPPA was tested prospectively in all patients in the independent validation cohort.…”
Section: Methodsmentioning
confidence: 99%